A cross-sectional survey of knowledge of malaria prevention among mobile and migrant populations in Cambodia. Issue 2 (2019) - Kheang, Soy Ty; Preston, Ashley; Collins, Emma Louise; An, Yom; Phalla, Hok; Ir, Por; Lek, Dysoley; Huy, Rekol; Siv, Sovannaroath; AlMossawi, Hala J; Kak, Neeraj
No abstract available